Loss of Neogenin alters branchial arch development and leads to craniofacial skeletal defects - Quilez, Sabrina; Dumontier, Emilie; Baim, Christopher; Kam, Joseph; Cloutier, Jean-François (Frontiers in Cell and Developmental Biology, 2024)
The formation of complex structures, such as the craniofacial skeleton, requires precise and intricate two-way signalling between populations of cells of different embryonic origins. For example, the lower jaw, or mandible, arises from cranial neural crest cells (CNCCs) in the mandibular portion of the first branchial arch (mdBA1) of the embryo, and its development is regulated by signals from the ectoderm and cranial mesoderm (CM) within this structure. The molecular mechanisms underlying CM cell influence on CNCC development in the mdBA1 remain poorly defined. Herein we identified the receptor Neogenin as a key regulator of craniofacial development. We found that ablation of Neogenin expression via gene-targeting resulted in several craniofacial skeletal defects, including reduced size of the CNCC-derived mandible. Loss of Neogenin did not affect the formation of the mdBA1 CM core but resulted in altered Bmp4 and Fgf8 expression, increased apoptosis, and reduced osteoblast differentiation in the mdBA1 mesenchyme. Reduced BMP signalling in the mdBA1 of Neogenin mutant embryos was associated with alterations in the gene regulatory network, including decreased expression of transcription factors of the Hand, Msx, and Alx families, which play key roles in the patterning and outgrowth of the mdBA1. Tissue-specific Neogenin loss of function studies revealed that Neogenin expression in mesodermal cells contributes to mandible formation. Thus, our results identify Neogenin as a novel regulator of craniofacial skeletal formation and demonstrates it impinges on CNCC development via a non-cell autonomous mechanism.